Determinants of Audit Report Lag and Corporate Governance in Malaysia - Kogilavani, Apadore (2012)
An accurate and timely financial statement is considered as an important aspect to the success of all organization. Therefore, financial information needs to be available to users especially investors and shareholders as soon as possible in their decision making. This paper aims to investigate the relationship between the characteristics of corporate governance; board independence, ownership concentration, audit committee independence, expertise, meeting, size, internal audit investment and audit report lag among companies listed under Bursa Malaysia. The samples covered are among 180 companies listed at Bursa Malaysia for 2009 and 2010. The samples are chosen randomly from 843 company of the population. Descriptive statistics was used to provide insight into the time taken by external auditors to complete an audit work of a company. The results show that on average, the companies took about 100 days to complete their audit report with a maximum and minimum day of 148 days and 26 days respectively . In addition regression analysis was used to provide empirical evidence on which variables had significant relationship with audit report lag. The results show that audit committee size, ownership concentration, organization size and profitability are significantly associated with audit report lag. However the other six variables (audit committee independence, meetings, expertise and types of auditors were found to have insignificant relationship with audit report lag.